Cell-specific nuclear import of plasmid DNA - Vacik, J (Gene Ther, 1999)
One factor limiting the success of non-viral gene therapy vectors is the relative inability to target genes specifically to a desired cell type. To address this limitation, we have begun to develop cell-specific vectors whose specificity is at the level of the nuclear import of the plasmid DNA. We have recently shown that nuclear import of plasmid DNA is a sequence-specific event, requiring the SV40 enhancer, a region known to bind to a number of general transcription factors. From these studies we developed a model whereby transcription factor(s) bind to the DNA in the cytoplasm to create a protein–DNA complex that can enter the nucleus using the protein import machinery. Our model predicts that by using DNA elements containing binding sites for transcription fac tors expressed in unique cell types, we should be able to create plasmids that target to the nucleus in a cell-specific manner. Using the promoter from the smooth muscle gamma actin (SMGA) gene whose expression is limited to smooth muscle cells, we have created a series of reporter plasmids that are expressed selectively in smooth muscle cells. Moreover, when injected into the cytoplasm, plas mids containing portions of the SMGA promoter localize to the nucleus of smooth muscle cells, but remain cytoplas mic in fibroblasts and CV1 cells. In contrast, a similar plasmid carrying the SV40 enhancer is transported into the nuclei of all cell types tested. Nuclear import of the SMGA promoter-containing plasmids could be achieved when the smooth muscle specific transcription factor SRF was expressed in stably transfected CV1 cells, supporting our model for the nuclear import of plasmids. Finally, these nuclear targeting sequences were also able to promote increased gene expression in liposome- and polycation-transfected non-dividing cells in a cell-specific manner, similar to their nuclear import activity. These results pro vide proof of principle for the development of cell-specific non-viral vectors for any desired cell type.